Inter- vs. Intra-Speaker Variation in Mixed Heritage Syntax: A Statistical Analysis - Cognola, Federica; Baronchelli, Ivano; Molinari, Evelina (Frontiers in Psychology, 2019)
Based on the novel data collected through original fieldwork on five syntactic phenomena (the position of the finite verb in embedded clauses, in sentences with a modal verb, negative concord, position of focused light/heavy objects in main clauses with a complex tense, scrambling) in the heritage language Mòcheno, we show that i) there exist two populations – one exhibiting intra-speaker variation between German and Italian word orders, and one lacking it; ii) these two populations are the result of diatopic variation and, to a lesser extent, of diastratic variation. The results reached through quantitative statistical analysis are partially convergent with those arrived at by traditional theoretical syntax on Mòcheno, but our analysis has allowed us to shed new light on a series of so-far neglected or poorly understood phenomena. More specifically, we discovered that there exists micro-variation fed by diastratic (age) variation within the Roveda variety, which represents the only case in Mòcheno in which age is a relevant factor in determining variation. We also showed that the traditional claim that the Palù variety is “more German” than the other Mòcheno variety is surely to be confirmed, but we could refine it by showing that German word orders are also accepted by speakers of other varieties and that the acceptability of these word orders in competition with the Italian syntax is not fed by the age of speakers (no diastratic variation). Finally, we showed that the acceptance of German word orders across speakers varies according to the phenomenon investigated: negation is the phenomenon in which German word orders are more likely to be accepted, whereas embedded clauses are the phenomenon in which German word orders are more likely to be rejected.